2017
DOI: 10.1007/s11262-017-1526-z
|View full text |Cite
|
Sign up to set email alerts
|

s8ORF2 protein of infectious salmon anaemia virus is a RNA-silencing suppressor and interacts with Salmon salar Mov10 (SsMov10) of the host RNAi machinery

Abstract: The infectious salmon anaemia virus (ISAV) is a piscine virus, a member of Orthomyxoviridae family. It encodes at least 10 proteins from eight negative-strand RNA segments. Since ISAV belongs to the same virus family as Influenza A virus, with similarities in protein functions, they may hence be characterised by analogy. Like NS1 protein of Influenza A virus, s8ORF2 of ISAV is implicated in interferon antagonism and RNA-binding functions. In this study, we investigated the role of s8ORF2 in RNAi suppression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Most interestingly, it has recently been demonstrated that s8ORF2 acts as a suppressor of RNA silencing (Thukral et al., ). Although the RNA‐binding property of the s8ORF2 has been predicted to be located mainly in the first 61 N‐terminal aa of the 241 aa protein (Garcia‐Rosada et al., ; Olsen et al., ), recent work by Thukral et al., provides evidence that the RNA‐binding domain is present in the region spanning 62 aa‐195 aa, which is lost in isolate CA/NL/G0010/2012. The reduced virulence of this isolate could thus be the result of unsuppressed host RNA silencing (Bohle, Lorenzen, & Schyth, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interestingly, it has recently been demonstrated that s8ORF2 acts as a suppressor of RNA silencing (Thukral et al., ). Although the RNA‐binding property of the s8ORF2 has been predicted to be located mainly in the first 61 N‐terminal aa of the 241 aa protein (Garcia‐Rosada et al., ; Olsen et al., ), recent work by Thukral et al., provides evidence that the RNA‐binding domain is present in the region spanning 62 aa‐195 aa, which is lost in isolate CA/NL/G0010/2012. The reduced virulence of this isolate could thus be the result of unsuppressed host RNA silencing (Bohle, Lorenzen, & Schyth, ).…”
Section: Discussionmentioning
confidence: 99%
“…The putative loss of function of this protein could greatly inhibit replication and consequently result in reduced virulence. Most interestingly, it has recently been demonstrated that s8ORF2 acts as a suppressor of RNA silencing (Thukral et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, immune evasion mechanisms for IFN type I response have been reported for fish viruses such as IPNV, where preVP2, VP3, VP4, and VP5 viral proteins inhibit IFNa1 activation ( 37 ). Similarly, s7ORF1 of ISAV inhibits IFN and Mx transcription, while s8ORF2, acting as RNA silencing suppressor, inhibits IFN production ( 38 40 ). Therefore, further studies are required to understand whether PRV displays mechanisms to antagonize the IFN type I responses and antiviral peptides observed in infected fish.…”
Section: Immune Response Against Prv Infectionmentioning
confidence: 99%
“…Multiple ISAV infection in vitro studies have been performed, describing a rapid interferon response (Andresen et al 2020; Samsing et al 2020) or the interplay between host and virus over the control of oxidative stress and apoptosis (Olavarria et al 2015a, b). In vitro studies have also been key to understand the role of the different ISAV proteins and their interaction with cellular mechanisms (Li et al 2016; Zhang et al 2017; Thukral et al 2018; Fredericksen et al 2019; Toro-Ascuy et al 2019).…”
Section: Introductionmentioning
confidence: 99%